2000
DOI: 10.5153/sro.528
|View full text |Cite
|
Sign up to set email alerts
|

Queer Frameworks and Queer Tendencies: Towards an Understanding of Postmodern Transformations of Sexuality

Abstract: This article aims to extend the theorization of postmodernity to consider social changes in the realm of sexuality. It offers a discussion of recent developments in queer theory, which, it is argued, can contribute significant new theoretical frameworks for the analysis of sexuality. It then traces some of the shifts in the organization of sexuality in the second half of the twentieth century, the emergence of modern sexual identities, and the changing relationships between ‘the homosexual’ and ‘the heterosexu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
79
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(85 citation statements)
references
References 29 publications
4
79
0
2
Order By: Relevance
“…Following Gosta Esping-Andersen's first typology of welfare regimes (EspingAndersen 1990), feminist critiques centred -justifiably -on his lack of attention to the unpaid care activities carried out by women in the domestic sphere (Lewis 1992;Daly and Rake 2003;Pfau-Effinger and Geissler 2005) and on the influence of these on their access to welfare benefits. Although some of the critical assessments of the initial welfare regimes typology did focus on their differential effects on women in particular kinds of living arrangements (particularly on lone mothers) (Daly 1994;Duncan and Edwards 1997;Lewis 1997;Duncan and Edwards 1999), the increasing diversity of intimate lives, and in particular the increase in the proportion of the population spending significant parts of their lives outside the conventional heterosexual cohabiting couple form (Roseneil, 2000), has never been a central consideration. Thus, it has been suggested that the ideological male breadwinner / female carer model of gender arrangements that dominated the second half of the 20 th century has largely been superseded by an equally normative idea(l) of the "dual breadwinner / dual carer", based on the premise that individuals will continue to live in households where two adults will divide paid and un-paid work between themselves, preferably on a relatively "de-gendered", equal and interchangeable basis (Le Feuvre 1999).…”
Section: Theoretical Contextualizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Following Gosta Esping-Andersen's first typology of welfare regimes (EspingAndersen 1990), feminist critiques centred -justifiably -on his lack of attention to the unpaid care activities carried out by women in the domestic sphere (Lewis 1992;Daly and Rake 2003;Pfau-Effinger and Geissler 2005) and on the influence of these on their access to welfare benefits. Although some of the critical assessments of the initial welfare regimes typology did focus on their differential effects on women in particular kinds of living arrangements (particularly on lone mothers) (Daly 1994;Duncan and Edwards 1997;Lewis 1997;Duncan and Edwards 1999), the increasing diversity of intimate lives, and in particular the increase in the proportion of the population spending significant parts of their lives outside the conventional heterosexual cohabiting couple form (Roseneil, 2000), has never been a central consideration. Thus, it has been suggested that the ideological male breadwinner / female carer model of gender arrangements that dominated the second half of the 20 th century has largely been superseded by an equally normative idea(l) of the "dual breadwinner / dual carer", based on the premise that individuals will continue to live in households where two adults will divide paid and un-paid work between themselves, preferably on a relatively "de-gendered", equal and interchangeable basis (Le Feuvre 1999).…”
Section: Theoretical Contextualizationmentioning
confidence: 99%
“…Specifically, we focus on the increasing deregulation and flexibilization of labour markets (Castel 1995;Sennett 1998;Beck 2000), the detraditionalization of intimate lives (Giddens, 1992(Giddens, , 1994Heelas et al, 1996;Beck and Beck-Gernsheim, 2002) and the increasing prevalence of lives led outside the conventional heterosexual couple form (Roseneil, 2000;Roseneil and Budgeon, 2004). Ulrich Beck, one of the leading proponents of the "individualization thesis" in European social theory argues that late or "second" modernity has largely "freed people from historically inscribed roles" (Beck, 2002: 202-203).…”
Section: Introductionmentioning
confidence: 99%
“…Lesbians and gay men have often been portrayed as pioneering pure relationships, plastic sexuality and friend-based personal communities (Giddens, 1992;Roseneil, 2000;Spencer and Pahl, 2006: 161-6). However, their relationship practices and perspectives are heterogeneous, highlighting both social continuities and change (Budgeon, 2008: 307;Weeks, 2007: 169, 184;Heaphy et al, 2012).…”
Section: Pioneers Of 'New' Ideals?mentioning
confidence: 99%
“…However, the extent to which the accepted existence of relationship-related diversity has been accompanied by changes in norms is disputed (Roseneil, 2000;Duncan and Smith, 2006;Weeks, 2007: 151). Jamieson (2004: 55) queries whether solo-living necessarily reflects coupledom declining as an ideal, and assessments of the implications of the growing importance of friendship networks for the normative role of exclusive sexual relationships vary markedly (Roseneil and Budgeon, 2004;Spencer and Pahl, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Återigen vill jag poängtera hur detta är tätt sammankopplat med de förutsättningar en har. Det kan också spela in att normer för hur relationer kan och bör se ut har luckrats upp under informanternas livstid (jmf Roseneil, 2000;Roseneil & Budgeon, 2004). Även i andra kvalitativa studier finns denna typ av erfarenheter representerade.…”
Section: Att Leva På Tvärs Med Tvåsamhetsnormerunclassified